Bridging Faith and Skills: An Analysis of EFL Students' Perceptions on Integrating Islamic Values with 21st Century Skills at Ma’had Aly Institution - Asifayanti; La Sunra (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
Integrating Islamic values with 21st-century skills in EFL education is increasingly essential to address contemporary educational challenges. This study investigates EFL students' perceptions of combining these values and skills within Ma’had Aly institutions, which emphasize cultural and spiritual identity. The research aims to explore the perceived importance of Islamic values, the integration of 21st-century skills from an Islamic perspective, and strategies to harmonize these dimensions in achieving holistic educational goals. Using a mixed-methods approach, data were collected through surveys, semi-structured interviews, and document reviews involving 15 purposively selected EFL students. Quantitative and qualitative analyses reveal that students prioritize Islamic values such as Talab al-Ilm (pursuit of knowledge), integrity, and ethics (72.7%). However, 54.5% expressed dissatisfaction with the current incorporation of 21st-century skills in their curriculum. Despite these limitations, over half of the participants reported working on developing these skills, and 63.6% acknowledged that integrating Islamic values with modern competencies significantly enhances their professional readiness and English proficiency. The study concludes that aligning Islamic values with 21st-century skills fosters a balanced educational paradigm addressing both spiritual and practical needs. Recommendations include strengthening mentorship, optimizing digital resource usage, and embedding Islamic principles into teaching practices to create inclusive, sustainable frameworks for future learning.